In-Service EFL Teachers’ Reflections on Their Instructional Practices: A Study in Indonesian Instructional Context - Irvan Effendi; Anita Triastuti (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. Reflective teaching is a means to improve teacher professionalism. By applying reflective teaching, teachers can not only find out their strengths and weaknesses during teaching, but also re-examine their principles and beliefs. In this regard, the purpose of this study is to determine the extent to which in-service EFL teachers understand the concept of reflective teaching, the reflection strategies they apply, and the obstacles that might hinder them in reflecting. This research is categorized as a descriptive-qualitative study which involved six junior high school in-service EFL teachers from four districts in Central Java and the Special Region of Yogyakarta. This study administered 3 data collection techniques, which are in-depth interviews, stimulated recall, and close-ended questionnaires as the data triangulation. The findings indicated that of the six participants, only two had heard or knew about the term reflective teaching. However, they have integrated reflection to their teaching practice and showed their ability to reflect within the level of dialogic reflection. Descriptive writing as the lowest level serves as their point of departure before they came to the higher levels (descriptive reflection and dialogic reflection). There was no evidence to show that the participants had reached the highest level of reflection, which is critical reflection. Further examination found that there were two major issues that hindered participants from reflecting, i.e. their lack of knowledge about the concepts and strategies of reflective teaching and a heavy number of administrative workload which reduced their reflection time.Keywords: Reflective Teaching, EFL, Reflective Practice, Reflection